Raman signatures of monoclinic distortion in (Ba1−xSrx)3CaNb2O9 complex perovskites. (18th July 2017) - Rodrigues, J. E.; Bezerra, D. M.; Costa, R. C.; Pizani, P. S.; Hernandes, A. C.
Abstract : Octahedral tilting is the most common distortion process observed in centrosymmetric perovskite compounds. Indeed, crucial physical properties of this oxide stem from the tilts of BO6 rigid octahedra. In microwave ceramics with perovskite‐type structure, there is a close relation between the temperature coefficient of resonant frequency and the tilt system of the perovskite structure. However, in many cases, limited access facilities are needed to assign correctly the space group, including neutron scattering and transmission electron microscopy. Here, we combine the Raman scattering and group theory calculations to probe the structural distortion in the perovskite (Ba1− x Sr x )3 CaNb2 O9 solid solution, which exhibits a structural phase transition at x  ≥ 0.7, from D3d 3 trigonal to C2h 3 monoclinic cell. Both phases are related by an octahedral tilting distortion (a 0 b − b − in Glazer notation). Low‐temperature Raman spectra corroborate the group‐theoretical predictions for Sr3 CaNb2 O9 compound because 36 modes detected at 25 K agree well with the 42 (25A g  ⊕ 17B g ) predicted ones. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : We combine the Raman scattering and group theory calculations to probe the structural distortion in the perovskite (Ba1− x Sr x )3 CaNb2 O9 solid solution, which exhibits a structural phase transition at x  ≥ 0.7, from D3d 3 trigonal to C2h 3 monoclinic cell. Both phases are related by an octahedral tilting distortion (a 0 b − b − in Glazer notation). Low‐temperature Raman spectra corroborate the group‐theoretical predictions for Sr3 CaNb2 O9 compound, because 36 modes detected at 25 K agree well with the 42 (25A g  ⊕ 17B g ) predicted ones.